2015
DOI: 10.1177/1070496515591578
|View full text |Cite
|
Sign up to set email alerts
|

Europeanization of Energy and Climate Policy

Abstract: In the course of the post-2020 climate and energy policy framework debate, the European Commission opened a new round in tackling a longstanding governance dilemma between European market integration and member states' discretion to develop policies according to domestically legitimized preferences. Motivated by ensuring welfare gains from an internal market, the attempts at the European Union level to strictly harmonize national support schemes for renewables ignore costs induced by the heterogeneity of prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Strunz, Gawel, and Lechmann [47] underline that the energy policy in the EU, on the whole, is diverse; some aspects are decentralized (e.g., nuclear policy), whilst some very Europeanized. Various researchers treat the energy policy Europeanization as the internal process within the EU [21,22], whilst some researchers try to focus on its external dimensions regarding non-EU member states. Samkharadze [9] observed that Georgia is affected by the EU energy policy.…”
Section: Theoretical Framework: Europeanization Processes Of the Eu Energy Policymentioning
confidence: 99%
“…Strunz, Gawel, and Lechmann [47] underline that the energy policy in the EU, on the whole, is diverse; some aspects are decentralized (e.g., nuclear policy), whilst some very Europeanized. Various researchers treat the energy policy Europeanization as the internal process within the EU [21,22], whilst some researchers try to focus on its external dimensions regarding non-EU member states. Samkharadze [9] observed that Georgia is affected by the EU energy policy.…”
Section: Theoretical Framework: Europeanization Processes Of the Eu Energy Policymentioning
confidence: 99%
“…In 2014, the German government decided to switch from a price-based to a volume-based support scheme. This fundamental instrumental shift was "forced" by external pressure (EU-Commission's State Aid Guidelines [3]) on the one side, but also by domestic debates about the affordability of the energy transition and the increasing costs of RE deployment on the other side (for more details on drivers and implications of this instrumental shift, see [4]).…”
Section: Occasion: Instrumental Shift In the Support Scheme For Renewmentioning
confidence: 99%
“…The third political change came from the EU Commission, which pressured the German federal government to change its feed‐in tariff to an auction system. The Commission had begun backing away from the EU's renewable energy targets in March 2013, to focus more on limiting short‐term costs and promoting market competition (Tews, , p. 4). Then, in December 2013, the Commission opened an investigation of Germany's renewable energy surcharge, including an infringement proceeding concerning the country's generous exemptions for industry, which it viewed as state aid subject to its supervision.…”
Section: Analysis Of the Four Subcasesmentioning
confidence: 99%
“…Then, in December 2013, the Commission opened an investigation of Germany's renewable energy surcharge, including an infringement proceeding concerning the country's generous exemptions for industry, which it viewed as state aid subject to its supervision. The Commission also issued draft guidelines on state aid for renewables, which labeled feed‐in tariffs as nonmarket compatible (Tews, , pp. 11, 13; Vogelpohl et al, , p. 52).…”
Section: Analysis Of the Four Subcasesmentioning
confidence: 99%
See 1 more Smart Citation